Pengaruh keselamatan dalam bekerja terhadap produktivitas pekerja pada pt musim mas - Khairun Na'im; Khamo Waruwu; Elyani Elyani; Jefri Nurdin (IICET (Indonesian Institute for Counseling, Education and Therapy), 2022)
The purpose of the study was to determine the effect of work safety consisting of the state of the work environment and the use of work equipment on worker productivity. This research was conducted at PT Musim Mas Medan, with a population and sample of 200 people taken by purposive sampling. The research instrument is a questionnaire/questionnaire with a Likert scale model. The requirement test was conducted to test for normality, multicollinearity test, and heteroscedasticity test. The data analysis technique used is multiple regression technique at a significance level of = 0.05. The results showed: there is a positive and significant effect between safety at work on worker productivity with t count = 3.617 and t table 1.97 with a coefficient value of 0.430. From the results of SPSS output, it is known that the R square value is 0.62 or 62%, which means that safety at work has an influence on the level of worker productivity.